Biological Risks of Using Non-Thermal Non-Ionizing Electromagnetic Fields - Olena Nizhelska; Lolita Marynchenko; Vasyl Piasetskyi (Innovative Biosystems and Bioengineering, 2020)
Electromagnetic pollution of the environment has become a significant environmental factor. The intensity of technogenic electromagnetic fields far exceeds the background indicators to which organisms have adapted in the course of evolution, in particular by their biorhythms. Much data on the biological effects of low-intensity (non-thermal) extremely high-frequency electromagnetic fields (EHF-EMF) at different levels of the organization has been accumulated. There are many possible explanations for these impacts, but the mechanism of action is not established. The purpose of this work is to analyze the negative effects of the use of non-thermal coherent electromagnetic radiation of extremely high frequencies. In particular, the use of microwave therapy is considered. A review of reports on the harmful effects of non-ionizing electromagnetic and magnetic fields among the population and professional groups has been made; the presence of the problem of hypersensitivity to such fields was shown. Information on the development of the direction of study of the resonant biological influence of EHF-EMF by Ukrainian specialists was provided. Particular attention is paid to the use of non-thermal microwaves for physiotherapy procedures, pain relief, correction of psycho-emotional disorders, ulcer healing, in particular stomach and duodenum, etc. It is noted that the so-called "therapeutic" frequencies of EHF-EMF, even if controlled, can cause negative effects, although they are not perceived as damaging. Changes in objective vital signs in the case of targeted exposure by low-intensity millimeter-wave radiation, namely, hemodynamics, temperature increase in the exposure zone, muscle activity, and the speed of the passage of a nerve impulse, an encephalogram were established. Precautionary recommendations based on the scientific and practical experience of using microwave acupuncture methods in the conditions of medical institutions are formulated. The synergistic effect of various influences, in particular electromagnetic fields, may not be a direct trigger of the disease, but a factor of not compensated stress. Therefore, clinical studies conducted many years ago cannot simply be dismissed on the grounds that the millimeter radiation penetrates only the outer layer of the skin. Skin cells can also secrete mediators that cause changes in ionic calcium channels and the level of calcium in the cells. The interest in these works is justified by the fact that currently the sources of monochromatic millimeter radiation will be spread with new communication systems. The risks of their biological action should be taken into account when emitters are installed.